2021
DOI: 10.3390/antiox10101610
|View full text |Cite
|
Sign up to set email alerts
|

Differential Yet Integral Contributions of Nrf1 and Nrf2 in the Human HepG2 Cells on Antioxidant Cytoprotective Response against Tert-Butylhydroquinone as a Pro-Oxidative Stressor

Abstract: In the past 25 years, Nrf2 (nuclear factor erythroid 2-related factor 2, also called NFE2L2) had been preferentially parsed as a master hub of regulating antioxidant, detoxification, and cytoprotective genes; albeit as a matter of fact that Nrf1 (nuclear factor erythroid 2-related factor 1, also called NFE2L1)—rather than Nrf2—is indispensable for cell homeostasis and organ integrity during normal growth and development. Herein, distinct genotypic cell lines (i.e., Nrf1α−/−, Nrf2−/−ΔTA, and caNrf2ΔN) are emplo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…Thereafter, these protein samples were collected and then subjected to measurement of their half-lives. In addition, trans -activity of Nrf1 and its mutants was determined by the pGL3-basic-6 × ARE-Luc reporter assay, as described previously [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thereafter, these protein samples were collected and then subjected to measurement of their half-lives. In addition, trans -activity of Nrf1 and its mutants was determined by the pGL3-basic-6 × ARE-Luc reporter assay, as described previously [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…However, the threshold of its generation or changes remains elusive to date, although it has been shown that the steady state of ER may be more easily disturbed [ 21 ]. Our previous work demonstrated differential and integral contributions of Nrf1 and Nrf2 to coordinately mediating distinct responsive gene expression profiles to the ER stressor tunicamycin (TU) [ 20 ] and pro-oxidative stressor tert -butylhydroquinone ( t BHQ) [ 22 ]. Recently, Nrf1, rather than Nrf2, was further identified as an indispensable redox-determining factor for mitochondrial homeostasis, in addition to the ER-associated proteostasis, by integrating multi-hierarchical responsive signaling pathways through nuclear respiratory gene controls towards mitochondrially located gene regulatory networks [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…To further investigate distinct roles for Nrf1 and Nrf2 in the nuclear-to-mitochondrial regulation, the experimental Nrf1α –/– , Nrf2 –/– and WT cell lines were treated with tert -butylhydroquinone [ t BHQ, as a pro-oxidative stressor (48)]. The results revealed that Nrf1, Nrf2, PGC1α, αPal NRF1 , GABPα NRF2 , and TFAM (Figure 3C, D, S6A, B) along with HO-1 and GCLM (Figure S6C) were significantly induced by t BHQ stimulation in WT cells.…”
Section: Resultsmentioning
confidence: 99%
“…Thereafter, these protein samples were collected, and then subjected to measuring their half-lives. In addition, trans -activity of Nrf1 and its mutants was determined by the pGL3-basic-6 × ARE-Luc reporter assay as described previously (20).…”
Section: Methodsmentioning
confidence: 99%
“…Thereby, Nrf1 has been identified as an important ER sensor for changes in the intracellular redox, glucose, protein and lipid (including cholesterol) (18,19). Our previous work demonstrated differential and integral contributions of Nrf1 and Nrf2 to coordinately mediating distinct responsive gene expression profiles to the ER stressor tunicamycin (TU) (19) and pro-oxidative stressor tert -butylhydroquinone ( t BHQ)(20). Recently, Nrf1, rather than Nrf2, is further identified as an indispensable redox-determining factor for mitochondrial homeostasis, in addition to the ER-associated proteostasis, by integrating multi-hierarchical responsive signaling pathways through those nuclearly-located respiratory gene controls towards mitochondrially-located gene regulatory networks (21).…”
Section: Introductionmentioning
confidence: 99%